Student Infractions in a Faith-Based Institution Analysis of Behavioral Trends and Disciplinary Responses - carpizo, cresencia; Ramos, Rowena Imelda; Rumarate , Emelito; Tayaben , Jun; Fernando , Mina; Amurao , Julio (12th International Scholars Conference 2025, 2026)
This descriptive quantitative study identified the common rule violations among students at a faith-based higher education institution in the Philippines during the 2024-2025 academic year. Analyses were done on 891 behavior records to identify the most frequent infractions and their links to demographic factors like sex, type of residence, and year level. The study also investigated the reasons behind these violations and the disciplinary measures taken. The findings showed that most infractions were minor. Curfew violations made up 29.5% of the cases, late food pick-up accounted for 21.9%, and improper grooming was 17.2%. Major offenses, like physical intimacy and sneaking out, were less frequent. Statistical tests indicated significant links between infractions and sex (χ² = 61.3, p < .001), type of residence (Likelihood Ratio = 380, p < .001), and year level (χ² = 149, p = .003). Late food pick-up happened almost equally among males and females. Improper grooming was predominant among females, while vaping was more rampant among males. Students living in dormitories had the highest number of violations related to curfew and grooming. First-year students showed the highest rates of infractions, which suggests they face adjustment challenges. Reasons for committing violations included poor time management, forgetfulness, and not being familiar with the rules. The institution mainly responded with redemptive and character-building approaches, providing counseling and spiritual guidance. These findings highlight the need for proactive, values-based programs focused on student growth in faith-based academic environments.